Analisis Kualitas Pelayanan Moda Transportasi Laut (KM Cantika Lestari 10C) Rute Ambon Weda - Irsan Bahdir; Juliet G. Metekohy; Febrino Wangean (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2026)
Sea transportation plays a vital role in supporting inter-island connectivity in Indonesia, particularly in archipelagic regions such as Maluku Province. As a region consisting of numerous islands, Maluku relies heavily on sea transportation to facilitate economic, social, and cultural activities. Therefore, the quality of sea transportation services is an important factor in ensuring passenger satisfaction and service sustainability. This study aims to evaluate the quality of sea transportation services on KM Cantika Lestari 10C operating on the Ambon–Weda route based on passenger perceptions, and to identify priority aspects for service improvement using the Importance Performance Analysis (IPA) method. The study employed a quantitative approach using questionnaire data collected from passengers. The IPA method was used to analyze the level of importance and performance of service attributes, which were then mapped into four quadrants to determine priority improvements. The results show that the average performance score of service quality is 86.06, indicating that the overall service is categorized as “very good.” Most service attributes meet passenger expectations; however, several aspects related to safety and security fall into priority improvement categories. These include routine inspection of the ship’s technical condition and ensuring that safety equipment such as lifebuoys, lifeboats, and fire extinguishers are in proper condition and easily accessible. In conclusion, the service quality of KM Cantika Lestari 10C is generally very good, but improvements in safety and security aspects are necessary to enhance passenger satisfaction and ensure sustainable service quality. Keywords: Sea Transportation; Service Quality; Importance Performance Analysis; Passenger Satisfaction; KM Cantika Lestari